The German Classics of the Nineteenth and Twentieth Centuries, Volume 04 : Masterpieces of German Literature Translated into English. in Twenty Volumes - Francke, Kuno, 1855-1930; Hölderlin, Friedrich, 1770-1843; Humboldt, Wilhelm von, 1767-1835; Jean Paul, 1763-1825; Kleist, Heinrich von, 1777-1811; Novalis, 1772-1801; Schlegel, August Wilhelm von, 1767-1845; Schlegel, Friedrich von, 1772-1829; Tieck, Ludwig, 1773-1853 (Salt Lake City, UT : Project Gutenberg, 2004)
"The German Classics of the Nineteenth and Twentieth Centuries, Volume 04" by Francke et al. is a collection of translated literary works that highlights significant contributions to German literature during the early 19th century. This volume delves into various authors, including Jean Paul, Wilhelm von Humboldt, and Novalis, showcasing a mixture of prose, essays, and dramatic works that reflect the philosophical and artistic shifts of that era. The opening of this volume introduces readers to the life and works of Jean Paul, offering insights into his childhood in Wunsiedel and his eventual development as an influential literary figure. It elaborates on his formative experiences, such as his struggle with poverty and his burgeoning interest in writing, leading to his eventual literary successes. The narrative provides a glimpse into his personal philosophy, characterized by deep sentiments and a unique perspective on the human experience, which resonates throughout his works, such as "Quintus Fixlein's Wedding" and "Titan." Overall, the beginning sets a thoughtful tone for the collection, inviting readers to explore the rich tapestry of German literature during this transformative period. (This is an automatically generated summary.)
The Life of Jean Paul. By Benjamin W. Wells. -- Quintus Fixlein's Wedding. -- Rome. -- The Opening of the Will. -- WILHELM VON HUMBOLDT Schiller and the Process of His Intellectual Development. -- The Early Romantic School. By James Taft Hatfield. -- AUGUST WILHELM SCHLEGEL Lectures on Dramatic Art. -- Introduction to Lucinda. By Calvin Thomas. -- Lucinda. -- Aphorisms. -- The Story of Hyacinth and Roseblossom. -- Aphorisms. -- Hymn to Night. -- Though None Thy Name Should Cherish. -- To the Virgin. -- Hyperion's Song of Fate. -- Evening Phantasie. -- Puss in Boots. -- Fair Eckbert. -- The Elves. -- The Life of Heinrich von Kleist. By John S. Nollen. -- Michael Kohlhaas. -- The Prince of Homburg.
Release date is 2004-04-01
Produced by Stan Goodman, Jayam Subramanian and PG Distributed Proofreaders
Keywords: German literature -- 19th century -- Translations into English; German literature -- 20th century -- Translations into English